Religious Inclusivism In Indonesia: Study of Pesantren An-Nida and Edi Mancoro, Salatiga, Central Java - Masroer Masroer (UIN Sunan Kalijaga Yogyakarta, 2018)
This abstract is the result of research intended to elaborate the students’ religious inclusiveness in the Nida and Edi Islamic boarding schools (Pesantren) of Salatiga, Central Java. In its descriptive analysis, this paper will try to elaborate a phenomenon or social unit of religious life in boarding schools in which some research instruments such as participant observation, open interviews and unstructured questionnaires are used. The results showed that: , there was a shift from the structured theoretical foundation both in Islamic boarding schools of Edi Mancoro and An Nida, an overview of students’ religious inclusiveness appearing in the form of culture, namely: cultural preservation to cultural transformation. The cultural forms emerge because the existence and function of religion (Islam) transforms into the culture while religion is analysed from the perspective of the local culture. The cultural and transformative inclusiveness is generated by the particularity of students’ religious and educational traditions although they maintained but they have also experienced changes; and openness to adapt and impart through a transformative social process. This transformation causes the emergence of collectively cultural values agreed and implemented together, thus they are universal. The students’ tradition preservation is determined by two mutually linked variables namely: 1) kiais as guardians of tradition, and 2) curriculum that maintains the teaching of classic book (Kitab Kuning (yellow book) as a buffer tradition. While the changes of tradition are also influenced by two variables, namely 1) social interaction with the surrounding local culture of the boarding schools, and 2) the students’ communication patterns with their external plural environment. , the students’ preseved and changing traditions prodused a unique religious authority . In the Pesantren An Nida, religious authority was manifested from the supermacy of fiqh (Islamic jurisprudence) enlightened by ijtihad (rational reasoning). There is a reciprocal relationship between fiqh and ijtihad, so that the dynamic verbal nature of fiqh will appear. The rational values in ijtihad was then strengthened — along with external changes — and accepted by the students’ perspective of jurisprudence. In the Pesantren Mancoro Edi, the research result showed that students’s complied religious authority was caused by the supermacy of dynamic fiqh enlightened by Sufism. The mystical value in Sufism also tends to be stronger — along with their contextual adaptation– thus affecting the students’ fiqh perspective. Unfortunately, the religious authorities seem to have paradoxical values because of their closeness to religious symbols outside their religion. It is therefore recommended that: a) to the students, they are supposed not to understand religion as a set of symbols, but a system of value, and if not, b) other religions are then welcomed into the local culture.[Artikel ini disusun dengan tujuan untuk memperoleh gambaran detil bagaimana inklusivitas keagamaan santri di Indonesia, khususnya di pondok pesantren An Nida dan Edi Mancoro Salatiga, Jawa Tengah. Dengan menggunakan analisis deskiptif interpretatif; yakni menggambarkan suatu fenomena yang ditafsirkan atau unit sosial tentang kehidupan keagamaan di pesantren, dan penggunaan instrumen riset berupa observasi partisipasi, wawancara terbuka dan angket tidak berstruktur. Artikel ini menjelaskan bahwa; pertama, terjadi pergeseran dari landasan teoritis yang disusun, baik di pesantren An Nida maupun Edi Mancoro, gambaran umum inklusivitas keagamaan santri yang muncul berbentuk budaya, yaitu dari kelestarian ke transformasi kultural. Bentuk budaya muncul karena eksistensi dan fungsi agama (Islam) itu masuk ke dalam kebudayaan; agama dilihat dari perspektif kebudayaan lokal. Inklusivitas yang bersifat transformasi kultural ini dihasilkan oleh partikularitas tradisi pendidikan keagamaan santri yang meskipun dipertahankan tetapi ia juga mengalami perubahan; keterbukaan untuk menerima dan memberi lewat proses sosial yang bersifat transformatif. Transformasi ini menciptakan nilai-nilai kultural yang disepakati dan diberlakukan bersama, dengan demikian bersifat universal. Kelestarian tradisi santri ditentukan oleh dua variabel yang saling berhubungan, yakni: 1) kiai sebagai penjaga tradisi, dan 2) kurikulum yang mempertahankan pengajaran kitab kuning (klasik) sebagai penyangga tradisi. Sementera perubahan tradisi dipengaruhi oleh dua variabel pula, yaitu 1) interaksi dengan sosial budaya lokal di mana pesantren itu berdiri, dan 2) pola komunikasi santri dengan lingkungan eksternal yang plural. Kedua, tradisi santri yang dipertahankan sekaligus mengalami perubahan itu menghasilkan otoritas keagamaan yang unik. Di pesantren An Nida, otoritas keagamaan itu terwujud dari supremasi fikih yang dicerahkan oleh ijtihad. Ada hubungan timbal balik antara fikih dengan ijtihad, sehingga watak verbalistik fikih mengalami dinamisasi. Nilai rasionalitas dalam ijtihad menguat –sejalan dengan perubahan di luaran- dan diterima menjadi cara pandang santri terhadap fikih. Di pesantren Edi Mancoro, memperlihatkan bahwa otoritas keagamaan yang dipatuhi santri terwujud dari supremasi fikih yang mengalami dinamisasi akibat tercerahkan oleh tasawuf. Nilai mistisisme yang terdapat di dalam tasawuf kemudian menguat pula –seiring dengan penyesuaiannya terhadap kontek- sehingga mempengaruhi cara pandang santri terhadap fikih. Tetapi otoritas keagamaan tersebut mengalami paradok karena ketertutupannya dengan simbol agama di luar santri. Oleh karena itu disarankan; a) kepada santri supaya tidak lagi memandang agama sebagai seperangkat simbol, tetapi sistim nilai, dan jika tidak, b) bagi agama lain agar dapat masuk ke dalam kebudayaan lokal setempat.]